2021
DOI: 10.1182/bloodadvances.2021004462
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of haploidentical and umbilical cord blood transplantation after myeloablative conditioning

Abstract: Haploidentical hematopoietic stem cell transplantation (haplo HSCT) has emerged as an important treatment modality. Most reports comparing haplo HSCT with post-transplant cyclophosphamide (PTCy) and other donor sources have focused on outcomes in older adults treated with reduced intensity conditioning. Therefore, in the current study, we evaluated outcomes in patients with hematological malignancy treated with myeloablative conditioning prior to haplo (n=375) or umbilical cord blood (UCB, n=333) HSCT. All hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…In the above study comparing the two ATG doses, the 3-year CIR was 17.6% and 15.3%, respectively, and the 3-year NRM was 20.2% and 24.4%, respectively (23). John et al (24) confirmed the lower relapse of cord blood transplantation than haploidentical transplantation by comparing the clinical outcomes of haploidentical transplantation and cord blood transplantation. The proportion of high-risk patients in our study was relatively high but not relapse was high, suggesting that haplo-cord-PBSCT may have a strong graft-versus-leukemia (GVL) effect; however, this finding needs to be substantiated with a large sample size in a paired randomized controlled trial.…”
Section: B C Amentioning
confidence: 91%
“…In the above study comparing the two ATG doses, the 3-year CIR was 17.6% and 15.3%, respectively, and the 3-year NRM was 20.2% and 24.4%, respectively (23). John et al (24) confirmed the lower relapse of cord blood transplantation than haploidentical transplantation by comparing the clinical outcomes of haploidentical transplantation and cord blood transplantation. The proportion of high-risk patients in our study was relatively high but not relapse was high, suggesting that haplo-cord-PBSCT may have a strong graft-versus-leukemia (GVL) effect; however, this finding needs to be substantiated with a large sample size in a paired randomized controlled trial.…”
Section: B C Amentioning
confidence: 91%
“…Barker reported rates of cGVHD that were less than 10%, even in the double cord setting, without serotherapy and where the median match was 5/8, and none were fully matched ( Barker et al, 2020 ). Wagner in his comparison of haplo-identical and cord blood transplants did not find any difference in rates of GVHD, even though the former is T-cell depleted and the latter are also significantly HLA-mismatched ( Wagner et al, 2021 ).…”
Section: Properties Of Cord Blood As a Donor Cell Source Relevant To ...mentioning
confidence: 99%
“…When HCT is being utilized as the curative approach for hematologic malignancies, HLA-mismatched UCB donor T-cells have characteristics that may lead to a reduced risk of relapse as compared to MSD [32], MUD [6 ▪▪ ], or haploidentical transplant [33], related to enhanced antitumor ability and cytotoxic CD8+ and CD4+ T-helper (Th1) profiles [34]. A higher CD8+ UCB content is associated with faster and higher myeloid and platelet engraftment, lower nonrelapse mortality (NRM), lower relapse, and increased overall survival (OS) [35].…”
Section: Special Immune Characteristics Of Umbilical Cord Blood Hemat...mentioning
confidence: 99%